(untitled) (Damascus University Journal of agriculture sciences, 2021)
This study aimed to assessment and analyzing of sheep market performance under the current circumstances in al-Hasakah governorate, the primary data for the average of the 2017/2018 and 2018/2019 were collected using a questionnaire designed for this purpose, distributed to the sample size of 313 rearers, they were selected simple random sampling way, one of the administrative areas of Al-Hasakah governorate, The results showed that there are eight markets in the study area, which different types of sheep are sold, which different in their size and the size of the deals that are held in them, and the number of dealers in them from one market to another, and the sale is done either on the basis of weight or head, and the value of the deals is paid either in cash or on The form of deferred payments, as well as the existence of multiple marketing patterns and margins through which sheep are marketed. The current circumstances have affected the sheep prices by 2.17 times and marketing costs by 6.24 times than they were before the crisis, and increase in production costs led to an increase in the rearers share of the consumer lira, and due to the lack of marketing operations applied to sheep, the marketing efficiency increased. Finally, it was found that there is a direct relationship between all the studied variables and the probability of selling sheep at the level of significance 5% on the one hand, and the numbers sold on the other hand, except for the variable distance to the nearest market that has an inverse relationship with it. The study recommends organizing and improving the current providing marketing and pricing information for rearers, and improving the level of marketing efficiency by reducing production and marketing costs, and raising the level of knowledge of rearers in the field of marketing.